An Examination of the Factors Affecting the Adoption of Digital Transformation by Librarians at Medical Universities Based on Rogers' Diffusion of Innovation Theory - Mohammadreza Azadifar; Afshin Hamdipour; Rasoul Zavaraqi; Hashem Atapour (Taṣvīr-i salāmat)
Background. Digital transformation refers to the changes resulting from the implementation of digital technologies across all aspects of human life. This study aims to explore the factors affecting the adoption of digital transformation by librarians at medical universities based on Rogers' Diffusion of Innovation (DoI) theory. Methods. This descriptive-correlational study involved 220 medical university librarians across the country, who were selected using a census sampling method. Data were collected during the third quarter of 2024 using a researcher-developed questionnaire. Five experts in knowledge and information science and social sciences confirmed the questionnaire’s validity, and a Cronbach’s alpha coefficient of 0.934 established its reliability. Data analysis was performed using SPSS 26, employing both descriptive and inferential statistical techniques, including factor analysis, Pearson’s correlation coefficient, and multiple regression analysis. Results. The study identified four of the five innovation adopter categories (innovators, early adopters, early majority, and late majority), while the laggards category was not observed. Factor analysis highlighted relative advantage, trialability, complexity, compatibility, and observability as main attributes of digital transformation. Furthermore, multiple regression analysis indicated that, among the predictor variables, observability and compatibility were significant predictors of digital transformation acceptance, collectively explaining 26% of the variance in the dependent variable. Conclusion. The results indicated that medical university librarians adopted digital transformation at a rate higher than average, showing a generally favorable attitude towards it. Most participants were categorized as early adopters of innovation. In accordance with Rogers' DoI theory, this study identified and validated the five key characteristics influencing digital transformation adoption. Moreover, these results have significant implications for policymakers and managers, highlighting the importance of promoting compatibility and observability features in digital transformation to accelerate the adoption rate.